2017
DOI: 10.1590/0004-282x20170042
|View full text |Cite
|
Sign up to set email alerts
|

Cranial venous sinus dominance: what to expect? Analysis of 100 cerebral angiographies

Abstract: We report an analysis of the cranial venous sinuses circulation, emphasizing morphological and angiographic characteristics. Methods: Data of 100 cerebral angiographies were retrospectively analyzed (p = 0.05). Results: Mean age was 56.3 years, 62% female and 38% male. Measurements and dominance are shown in the Tables. There was no association between age or gender and dominance. Right parasagittal division of the superior sagittal sinus was associated with right dominance of the transverse sinus, sigmoid sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
(26 reference statements)
3
12
0
1
Order By: Relevance
“…Seventy-four percent of the paired specimens revealed SS dominance on the right side. These results coincide with findings in the literature that the SS is frequently larger on the right side [19, 21, 22, 24]. The specific distances analyzed in this study were chosen based on those most applicable to neurotologic surgical approaches.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Seventy-four percent of the paired specimens revealed SS dominance on the right side. These results coincide with findings in the literature that the SS is frequently larger on the right side [19, 21, 22, 24]. The specific distances analyzed in this study were chosen based on those most applicable to neurotologic surgical approaches.…”
Section: Discussionsupporting
confidence: 87%
“…There have been many cadaveric [1820, 2330] and radiologic [21, 22, 26, 31–36] studies investigating the variability of the SS, as well as its anatomic relationships to other structures within the temporal bone. However, the intricacies of temporal bone anatomy can make morphological analysis in two-dimensions (2D) challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The goal is to provide possible measurement parameters for the clinical treatment of suspected thrombosis or the identification of anatomical variations. The average diameters of TS obtained by Manara et al were 6.5 mm ± 1.84 on the right side and 5.1 mm ± 1.72 on the left side (P < 0.0001) (Manara et al, 2010), which were the same as the values of TS measured by Kitamura et al using DSA (right,6.4 mm vs. left, 5.4 mm) (Kitamura et al, 2017), but both were larger than those obtained by Baikov et al The average diameters observed by them were 5.34 mm on the right side and 4.73 mm on the left (Baikov et al, 2007). All studies confirmed that the right TS had a larger diameter than the left TS, and no study in the cohort of Manara et al had a right-left mean diameter <3 mm.…”
Section: Imaging Anatomy Of the Cerebral Venous Systemsupporting
confidence: 79%
“…Interestingly, the presence of the parasagittal right division of the SSS was correlated with the right dominance of the transverse sinus (TS), straight sinus (SS), and IJV, while the presence of the parasagittal left division of the SSS was correlated with the left dominance of the TS, SS, and IJV, both of which were statistically significant. Epidemiological factors such as age and sex did not affect venous sinus drainage patterns in this cohort ( Kitamura et al, 2017 ). Angiographic results in the venous phase in a study by Zouaoui et al confirmed that the absence of the entire lateral sinus (transverse or sigmoid) is not equivalent to lateral sinus thrombosis, which may be due to embryonic hypoplasia and creates venous drainage dominance on the non-deleted side ( Zouaoui and Hidden, 1988 ).…”
Section: Imaging Anatomy Of the Cerebral Venous Systemmentioning
confidence: 67%
“…The location, as well as the size and shape of these vasculatures, such as sigmoid sinus (SS) and jugular bulb (JB) (a connection between the SS and the internal jugular vein), is highly variable, including a significant difference in laterality 2 , 4 6 . The pneumatization of the TB has been reported to be responsible for these variabilities 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%